A Bibliometric Analysis of Digital Economy in India using Network and Density Visualization (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The goal of the "digital economy" is to boost economic activity by using information and communication technologies to create digital data. In order to support the emerging digital economy, technology for digital computing has been created across a variety of digital platforms through internet-based company development.To fully realise the vision of Viksit Bharat@2047, India's digital economy must grow and be strengthened.The goal of the current study is to offer a thorough overview utilising bibliometric analysis from the Dimensions database, drawing from the body of existing literature on the digital economy. Using VOSviewer, this study maps out the trends in the digital economy. The study's conclusions, which included annual publications, the top contributing authors, the journal and affiliation, the subject matter, the type of publication, citations each year, and the top publishing nation, provided insightful information.The results of the analysis show that a number of topics, such as artificial intelligence, digital payments, unified payment interfaces (UPI), sharing economies, digital platforms, knowledge economies, cashless transactions, demonetization, and financial technology, have a high level of novelty elements and have the potential to be developed in a variety of sectors to support economic growth. Further research is necessary on a number of new problems, especially those related to the growth of the digital or electronic economy, in order to find solutions that meet the needs of the modern world while using rapidly advancing knowledge and technology.